Exploration of Scientific Reasoning Skills Students’ on Material Growth and Development of Plants Class XII MIPA Based Gender at SMAN Ambulu Jember - Nadifah, Ainun; Wardani, Imaniah Bazlina (Aspirasi Masyarakat Intelektual Islam Nusantara, 2024)
Education is an important element for a person's life in any country. Indonesia has taken the Program for International Student Assessment (PISA) test since 2001. Since then, Indonesia's scores in science have fluctuated but have remained flat. So, scientific reasoning skills are needed that can help students understand science, especially in biology. Moreover, scientific reasoning skills are standard substance for graduates as stated in Minister of Education and Culture Regulation Number 21 of 2016. The purpose of research is to describe the scientific reasoning skills of male and female students on material plant growth and development class XII MIPA 3 at SMAN Ambulu Jember. The research method used is a qualitative for case study type. The research location chosen was SMAN Ambulu Jember. The subjects were selected using purposive sampling technique. The data collection techniques are tests, interviews, observation and documentation. The data analysis technique used of Miles and Huberman Model qualitative data analysis which consists of 4 stages are data collection, data condensation, data display and conclusion drawing/verification. Based on the results, scientific reasoning skills of male and female students are good category. From the test results, there are 7 male students belonging to transitional operational patterns, while there are 5 male students belonging to formal operational patterns. The female students belonging to the formal operational patterns are 18 people and 6 female students with the transitional operational patterns. In conclusion, this study sheds light on the commendable scientific reasoning skills demonstrated by both male and female students in understanding material on plant growth and development in class XII MIPA 3 at SMAN Ambulu Jember.